2020
DOI: 10.1016/j.scijus.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic reporting in criminal cases in the United States: A baseline study

Abstract: Over a decade ago, the National Research Council (NRC) Report, Strengthening Forensic Science in the United States, highlighted the lack of standards with regard to reporting of evidence in forensic science: [M]any terms are used by forensic examiners in reports and in court testimony to describe findings, conclusions, and the degrees of association between evidentiary material (e.g., hairs, fingerprints, fibers) and particular people or objects. Such terms include but are not limited to " match," " consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Cole and Barno [ 15 ] examined expert reports and transcripts regarding friction ridge prints (91 reports), firearms and toolmarks (48), questioned documents (52), and shoeprint comparisons (381 reports from CTS), obtained from a variety of sources (e.g., a search of Westlaw for expert materials), in the United States. Of the 48 firearm and toolmark reports, 28 (58%) reported an identification, 14 (29%) reported an inconclusive, and 6 (13%) reported an exclusion.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Cole and Barno [ 15 ] examined expert reports and transcripts regarding friction ridge prints (91 reports), firearms and toolmarks (48), questioned documents (52), and shoeprint comparisons (381 reports from CTS), obtained from a variety of sources (e.g., a search of Westlaw for expert materials), in the United States. Of the 48 firearm and toolmark reports, 28 (58%) reported an identification, 14 (29%) reported an inconclusive, and 6 (13%) reported an exclusion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All of the firearm and toolmark examiner reports followed the AFTE range of conclusions (i.e., identification, inconclusive, or exclusion). Cole and Barno [ 15 ] concluded that they overall “found relatively few probabilistic reports. The probabilistic reports that we did find were almost entirely 'Inconclusive' reports which, by their very nature, were always coded as probabilistic (p. 412).”…”
Section: Literature Reviewmentioning
confidence: 99%
“…Curran [ 1 ] lamented that only 13% of laboratories surveyed used the likelihood-ratio framework for glass evidence , but this may be one of the highest rates of adoption after DNA. In many other branches of forensic science the rate of adoption of the likelihood-ratio framework by practitioners is near zero (Bali et al [ 48 ]; Cole & Barno [ 49 ]).…”
Section: A Paradigm Shift In Evaluation Of Forensic Evidencementioning
confidence: 99%
“…If a latent print is searched in AFIS, examiners subsequently make one of three conclusions depending on the AFIS candidate list outcome 4 and further examination. Examiners may conclude that there is No Association, meaning the latent print does not appear to correspond to any print on the AFIS candidate list.…”
Section: Hfsc Laboratory Proceduresmentioning
confidence: 99%
“…For instance, inconclusive determinations on low quality prints are likely to be more "accurate" than inconclusive determinations for higher quality prints. The ambiguity about how best to evaluate these inconclusive decisions also speaks to the importance of shifting away from categorical outcomes generally and towards reporting conclusions probabilistically, though the practice is not currently the norm in latent print comparisons [4].…”
Section: Limitations and Future Researchmentioning
confidence: 99%